2010
DOI: 10.1002/app.33002
|View full text |Cite
|
Sign up to set email alerts
|

Chemical structure of poly(β‐cyclodextrin‐co‐citric acid)

Abstract: We synthesized water-insoluble polymers, poly(b-cyclodextrin-co-citric acid)s, by heating a mixture of citric acid, cyclodextrin (CD), and Na 2 HPO 4 as a catalyst with a 6 : 1 : 2 molar ratio at 160, 170, and 180 C for 10 and 20 min. The chemical composition of the polyesters was determined by high pressure liquid chromatography (HPLC) analysis of the polymer hydrolysates. The crosslinking mechanisms and thermal degradation of the polymers were also investigated. The polyesters contained 30-35% citric acid, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Such adsorbed carboxylate species [R (COO -) x ] ads can be interpreted as fingerprints of the original citrate ions that might have decompose under the temperature and pressure regime used for Hap synthesis, in line with the reports on citric acid thermal degradation[36][37][38][39] . The band at 1384 cm -1 may be ascribed to CH 2 scissoring and carboxylate groups differently coordinated to Hap surface under monodentate or bidentate configurations 6,30 may account for the bands at 1402, 1458, 1577 and 1669 cm -1 .…”
supporting
confidence: 68%
“…Such adsorbed carboxylate species [R (COO -) x ] ads can be interpreted as fingerprints of the original citrate ions that might have decompose under the temperature and pressure regime used for Hap synthesis, in line with the reports on citric acid thermal degradation[36][37][38][39] . The band at 1384 cm -1 may be ascribed to CH 2 scissoring and carboxylate groups differently coordinated to Hap surface under monodentate or bidentate configurations 6,30 may account for the bands at 1402, 1458, 1577 and 1669 cm -1 .…”
supporting
confidence: 68%
“…Therefore, we modified the surface of the electrospun PET nanofibers through the polymerization reaction between CTR and CD [21,24,25]. Water-insoluble cyclodextrin polymer (CDP) network was formed by the crosslinking reaction between CD and CTR [26]. Three different types of native CD (␣-CD, ␤-CD and ␥-CD) were used to form ␣-CDP, ␤-CDP and ␥-CDP.…”
Section: The Cdp Formation Onto Electrospun Pet Nanofibersmentioning
confidence: 99%
“…The citrate contribution to the particle surface charge will be ruled by the amount of free carboxylate groups negatively charged, which in turn is conditioned by the citrate coordination mode to Hap surface. Moreover, it was already reported that citric acid may degrade at T .1458C [35,36] leading to reaction products that include different dehydroxylated or decarboxylated acids and anhydrides depending on the used heating rate and temperature. It is thus hypothesized that the original citrate ions do not exist as adsorbed species on the HS particle surface, but instead as smaller carboxylated ions resulting from citrate ion decomposition under the high temperature and pressure used for Hap hydrothermal synthesis.…”
mentioning
confidence: 99%